2009
DOI: 10.1071/an09005
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the melanocortin-1 receptor gene in alpaca and identification of possible markers associated with phenotypic variations in colour

Abstract: The aim of this study was to determine if any correlation exists between melanocortin-1 receptor (MC1R) polymorphisms and skin and fibre colour in alpacas. Primers capable of amplifying the entire alpaca MC1R gene were designed from a comparative alignment of Bos taurus and Mus musculus MC1R gene sequences. The complete MC1R gene of 41 alpacas exhibiting a range of fibre colours, and which were sourced from farms across Australia, was sequenced from PCR products. Twenty-one single nucleotide polymorphisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 58 publications
4
46
1
6
Order By: Relevance
“…In previous studies, Feeley & Munyard (2009) reported that alpacas showing white fleece were heterozygotes for this polymorphism and that GG genotype animals presented a lack of eumelanin in the skin, in accordance with the results in our work. In previous studies, Feeley & Munyard (2009) reported that alpacas showing white fleece were heterozygotes for this polymorphism and that GG genotype animals presented a lack of eumelanin in the skin, in accordance with the results in our work.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In previous studies, Feeley & Munyard (2009) reported that alpacas showing white fleece were heterozygotes for this polymorphism and that GG genotype animals presented a lack of eumelanin in the skin, in accordance with the results in our work. In previous studies, Feeley & Munyard (2009) reported that alpacas showing white fleece were heterozygotes for this polymorphism and that GG genotype animals presented a lack of eumelanin in the skin, in accordance with the results in our work.…”
supporting
confidence: 93%
“…Each animal of a colour group was chosen from a different herd. Eight of these 18 SNPs (c.82A>G, c.126T>C, c.258A>G, c.354T>C, c.376A>G, c.618G>A, c.901C>T and c.933G>A), all in the CDS, had been described previously (Powell et al 2008;Feeley & Munyard 2009), while 10 polymorphisms had never been described before. Five measurements were taken for each sample to obtain the average.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of the melanocortin-1 receptor (MC1R) and agouti signaling protein (ASIP) genes in alpacas of different coat colors revealed several polymorphisms that may be predictive of coat color [14-18]. Powell et al reported that the M87V and S126G variants of MC1R may affect coat color with brown coat color animals showing homozygosity for the methionine and serine alleles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including those we conducted, demonstrated that the three pigmentation critical enzymes, namely, tyrosinase (Tyr), tyrosinase-related protein 1 (Tyrp1), tyrosinaserelated protein 2 (DCT), and the critical factors, which include melanocortin-1 receptor protein (Mc1r), inducible nitric oxide synthase, micropthalmia-associated transcription factor (MITF), solute carrier family 7 member 11(Slc7a11), and ␤-catenin, were stimulators of melanogenesis in alpaca and agouti signaling proteins (Asip), miR-25 and miR-137 were inhibitors of melanogenesis in alpaca (Feeley and Munyard, 2009, Zhu, 2010, Chandramohan, 2013, Dong, 2012, Xue et al, 2014.…”
Section: Introductionmentioning
confidence: 99%